2020
DOI: 10.1158/1538-7445.sabcs19-pd1-06
|View full text |Cite
|
Sign up to set email alerts
|

Abstract PD1-06: Open label phase 1b/2 study of ladiratuzumab vedotin in combination with pembrolizumab for first-line treatment of patients with unresectable locally-advanced or metastatic triple-negative breast cancer

Abstract: Background Ladiratuzumab vedotin (LV) is an investigational anti-LIV-1 antibody-drug conjugate with a protease-cleavable linker to monomethyl auristatin E (MMAE). LIV-1 is highly expressed in metastatic triple negative breast cancer (TNBC). LV mediated delivery of MMAE drives antitumor activity through cytotoxic cell killing and has been shown to induce immunogenic cell death (ICD). LV monotherapy has demonstrated encouraging activity in TNBC. Anti-PD-(L)1 agents are emerging as part of the TNBC treatment para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 0 publications
0
24
0
Order By: Relevance
“…Furthermore, ladiratuzumab-vedotin, an ADC against the membrane zinc transporter protein LIV-1, is under investigation in several clinical trials (Table 1). Preliminary results have been observed with the combination of ladiratuzumab-vedotin and pembrolizumab in heavily pretreated TNBC patients, with 54% of ORR 170 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, ladiratuzumab-vedotin, an ADC against the membrane zinc transporter protein LIV-1, is under investigation in several clinical trials (Table 1). Preliminary results have been observed with the combination of ladiratuzumab-vedotin and pembrolizumab in heavily pretreated TNBC patients, with 54% of ORR 170 .…”
Section: Introductionmentioning
confidence: 99%
“…Ladiratuzumab vedotin (LV) targets LIV-1, a transmembrane cell adhesion molecule highly overexpressed in TNBC. The drug’s payload is the microtubule disrupting agent-monomethyl auristatin E. A Phase 1b/2 trial of LV in combination with pembrolizumab was investigated in a treatment naïve population with metastatic TNBC[ 78 ]. The trial was based on the biological rationale for a synergistic effect of the addition of two immune modulating agents in the first-line setting.…”
Section: Germline Brca1/brca2 Mutationsmentioning
confidence: 99%
“…In this ongoing trial, 26 patients were assessed, and the confirmed OR rate was 54%. The most common TEAEs were diarrhea, fatigue, hypokalemia, alopecia nausea and constipation [67].…”
Section: Marine-derived Compounds In Phase II Clinical Statusmentioning
confidence: 99%